Where the Red-Winged Blackbirds Sing : The Akimel O'odham and Cycles of Agricultural Transformation in the Phoenix Basin - Bess, Jennifer; Bess, Jennifer (Book collections on Project MUSE., 2021)
"Examines the ways in which the Akimel O'odham ("River People") and their ancestors, the Huhugam, adapted to economic, political, and environmental constraints imposed by federal Indian policy, the Indian Bureau, and an encroaching settler population in Arizona's Gila River Valley"